A degradable film and preparation method thereof

By using PLA, secondary aminosilane modified starch, PBAT, hydroxymethylsilane modified starch and nitrile-containing compounds in the film, the mechanical properties of high-starch content biodegradable films are improved, and the film is easily damaged. Problem, achieving higher tensile loads and right-angle tear strength.

CN118617836BActive Publication Date: 2025-01-03HEBEI KELUN PLASTIC TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410999776.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-24
Publication Date
2025-01-03
Estimated Expiration
2044-07-24

AI Technical Summary

Technical Problem

The high-starch content biodegradable film has poor mechanical properties, which leads to the film being easily damaged.

Method used

A degradable film structure consisting of a surface layer, an intermediate layer and a base layer, wherein the surface layer contains PLA and secondary aminosilane modified starch, the intermediate layer contains PBAT, PLA and hydroxymethylsilane modified starch, and the base layer contains PBAT and nitrile. The compound of the group and hydroxymethylsilane modified starch improve compatibility and binding strength by combining the modified starch and nitrile-containing compound to avoid layer separation.

Benefits of technology

It significantly improves the strength of the degradable film, meets the tensile load and right-angle tear load indicators of GB/T 35795-2017, and enhances the mechanical properties of the film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of degradable materials, and proposes a degradable film and a preparation method thereof. A degradable film comprises a surface layer, an intermediate layer and a base layer from top to bottom, wherein the raw materials of the surface layer comprise the following components in parts by mass: 60-80 parts of PLA, 3-8 parts of secondary aminosilane-modified starch; the raw materials of the intermediate layer comprise the following components in parts by mass: 70-90 parts of PBAT, 15-35 parts of PLA, 10-20 parts of hydroxymethylsilane-modified starch; the raw materials of the base layer comprise the following components in parts by mass: 10-30 parts of PBAT, 0.5-3.5 parts of a compound containing a nitrile group, and 7-12 parts of hydroxymethylsilane-modified starch. Through the above technical scheme, the problem of poor mechanical properties of high-starch-content biodegradable films in the related art is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of degradable materials, and in particular to a degradable film and a preparation method thereof. Background Art

[0002] Degradable film is a new type of film produced to meet the society's need for environmental protection. It refers to a film material that can be split and degraded in the natural environment. It not only has the functions and characteristics of traditional plastics, but can also be degraded by microorganisms or ultraviolet rays after reaching the end of its service life. It has been widely used in agriculture, food, medicine and other fields.

[0003] The types of degradable films are mainly divided into photodegradation, photobiodegradation, photooxidative biodegradation, high starch content biodegradation, high calcium carbonate filled photooxidative degradation, full biodegradation, etc. Among them, the most commonly used is high starch content biodegradable film, but the mechanical properties are poor, resulting in easy damage to the film. Summary of the invention

[0004] The invention provides a degradable film and a preparation method thereof, which solves the problem of poor mechanical properties of high-starch-content biodegradable films in the related art.

[0005] The technical solution of the present invention is as follows:

[0006] A degradable film comprises a surface layer, an intermediate layer and a base layer from top to bottom, wherein the raw materials of the surface layer comprise the following components in parts by weight: 60-80 parts of PLA and 3-8 parts of secondary aminosilane modified starch;

[0007] The raw materials of the intermediate layer include the following components in parts by weight: 70-90 parts of PBAT, 15-35 parts of PLA, and 10-20 parts of hydroxymethylsilane-modified starch;

[0008] The raw materials of the base layer include the following components in parts by weight: 10 to 30 parts of PBAT, 0.5 to 3.5 parts of a compound containing a nitrile group, and 7 to 12 parts of hydroxymethylsilane-modified starch.

[0009] In the present invention, PBAT is a copolymer of butylene adipate and butylene terephthalate, and PLA is polylactic acid.

[0010] The compound containing a nitrile group in the present invention can be any compound containing a nitrile group, preferably one or more of p-toluonitrile, phthalonitrile, glutaronitrile, 1,2-phenylenedicarbonitrile, 1,4-phenylenedicarbonitrile, terephthalonitrile, isophthalonitrile, and 4-cyanopimelonitrile.

[0011] As a further technical solution, the mass ratio of hydroxymethylsilane-modified starch to the compound containing nitrile groups in the base layer is 9:1.5-2.5.

[0012] The present invention limits the mass ratio of the hydroxymethylsilane-modified starch to the compound containing the nitrile group in the base layer to 9:1.5-2.5, thereby further improving the strength of the degradable film.

[0013] As a further technical solution, the compound containing a nitrile group is a compound containing two nitrile groups, preferably one or more of phthalonitrile, glutaronitrile, 1,2-phenylenedicarbonitrile, 1,4-phenylenedicarbonitrile, terephthalonitrile, and isophthalonitrile.

[0014] The present invention limits the compound containing nitrile groups to compounds containing two nitrile groups, thereby further improving the strength of the degradable film.

[0015] As a further technical solution, the mass ratio of the secondary aminosilane modified starch to the hydroxymethylsilane modified starch in the middle layer is 5:12-17.

[0016] The present invention limits the mass ratio of the secondary aminosilane modified starch to the hydroxymethylsilane modified starch in the middle layer to 5:12-17, thereby further improving the strength of the degradable film.

[0017] As a further technical solution, the compound containing a nitrile group includes a compound containing a benzene ring and a nitrile group and a compound containing no benzene ring and a nitrile group in a mass ratio of 2:0.5.

[0018] The present invention limits the compound containing nitrile groups to compounds containing benzene rings and nitrile groups and compounds containing no benzene rings and nitrile groups in a mass ratio of 2:0.5, thereby further improving the strength of the degradable film.

[0019] As a further technical solution, the raw materials of the hydroxymethylsilane-modified starch in the base layer include hydroxymethylsilane and starch in a mass ratio of 1 to 5:100.

[0020] As a further technical solution, the raw materials of the secondary aminosilane-modified starch in the surface layer include secondary aminosilane and starch in a mass ratio of 1 to 5:100.

[0021] As a further technical solution, the raw materials of the hydroxymethylsilane-modified starch in the middle layer include hydroxymethylsilane and starch in a mass ratio of 1 to 5:100.

[0022] The secondary aminosilane in the present invention can be any silane containing a secondary amino group, preferably one or both of N-aminoethyl-3-aminopropyltriethoxysilane and (butylaminomethyl)triethoxysilane.

[0023] The hydroxymethyl silane in the present invention can be any silane containing hydroxymethyl, preferably one or both of N-(hydroxyethyl)-N-methylaminopropyltrimethoxysilane and 3-[bis(2-hydroxyethyl)amino]propane-triethoxysilane.

[0024] The invention also proposes a method for preparing a degradable film, comprising the following steps: respectively melting and mixing the raw materials of the surface layer, the raw materials of the middle layer and the raw materials of the base layer, co-extruding, blow molding, and cooling to obtain the degradable film.

[0025] The invention also proposes the application of the degradable film or the degradable film prepared by the preparation method in ground film.

[0026] The working principle and beneficial effects of the present invention are:

[0027] The present invention provides a degradable film, which includes a surface layer, an intermediate layer and a base layer from top to bottom, wherein the raw materials of the surface layer include PLA and secondary aminosilane modified starch, the raw materials of the intermediate layer include PBAT, PLA and hydroxymethylsilane modified starch, and the raw materials of the base layer include PBAT, a compound containing a nitrile group and hydroxymethylsilane modified starch. Wherein the starch can improve the compatibility of starch with PLA after being modified by secondary aminosilane, and the starch can improve the compatibility of starch with PBAT and PLA after being modified by hydroxymethylsilane, and at the same time, a compound containing a nitrile group is added to the base layer, and the nitrile group can not only react with the ester group in PBAT, but also react with the hydroxymethyl in the hydroxymethylsilane modified starch during processing, thereby improving the compatibility inside the base layer and also improving the bonding strength between the base layer and the intermediate layer. In addition, during processing, the secondary amino group in the secondary aminosilane modified surface layer can react with the hydroxymethyl in the hydroxymethylsilane modified starch in the intermediate layer, which can improve the bonding strength between the surface layer and the intermediate layer, so that the entire degradable film is not prone to layer separation, thereby achieving the effect of improving the strength of the degradable film. DETAILED DESCRIPTION

[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] The parameters of the raw materials in the following examples and comparative examples are as follows:

[0030] The starch is native cassava starch, with a 25°C, 6wt% aqueous solution viscosity ≥130cp;

[0031] PBAT is PBAT TH801T;

[0032] PLA is PLA LX175.

[0033] Example 1

[0034] S1, adjusting the pH value of 100 g of cassava starch to 9 with sodium carbonate aqueous solution, drying at 45° C. to a water content of 3 wt %, adding 3 g of (butylaminomethyl)triethoxysilane and stirring for 10 min, heating to 135° C. and reacting for 45 min, cooling, and grinding to obtain secondary aminosilane-modified starch;

[0035] S2, adjusting the pH value of 100 g of cassava starch to 9 with sodium carbonate aqueous solution, drying at 45° C. to a water content of 3 wt %, adding 3 g of N-(hydroxyethyl)-N-methylaminopropyltrimethoxysilane, stirring for 10 min, heating to 135° C., reacting for 45 min, cooling, and grinding to obtain hydroxymethylsilane-modified starch;

[0036] S3, mixing 70 parts of PLA and 5 parts of secondary aminosilane-modified starch at 175° C. to obtain a surface layer raw material;

[0037] S4, 80 parts of PBAT, 25 parts of PLA, and 10 parts of hydroxymethylsilane-modified starch were mixed uniformly at 175° C. to obtain a middle layer raw material;

[0038] S5, 20 parts of PBAT, 0.5 parts of p-toluonitrile, and 9 parts of hydroxymethylsilane-modified starch were mixed uniformly at 130° C. to obtain a base material;

[0039] S6. Co-extrude the surface layer raw material, the middle layer raw material and the base layer raw material at 180° C., blow mold, and cool to obtain a degradable film with a thickness ratio of surface layer: middle layer: base layer of 0.3:4:0.7.

[0040] Example 2

[0041] S1, adjusting the pH value of 100 g of cassava starch to 9 with a sodium carbonate aqueous solution, drying at 45° C. to a water content of 3 wt %, adding 1 g of N-aminoethyl-3-aminopropyltriethoxysilane, stirring for 10 min, heating to 135° C. to react for 45 min, cooling, and grinding to obtain secondary aminosilane-modified starch;

[0042] S2, adjusting the pH value of 100 g of cassava starch to 9 with a sodium carbonate aqueous solution, drying at 45° C. to a water content of 3 wt %, adding 1 g of 3-[bis(2-hydroxyethyl)amino]propane-triethoxysilane, stirring for 10 min, heating to 135° C., reacting for 45 min, cooling, and grinding to obtain hydroxymethylsilane-modified starch;

[0043] S3, mixing 60 parts of PLA and 3 parts of secondary aminosilane-modified starch at 175° C. to obtain a surface layer raw material;

[0044] S4, mixing 70 parts of PBAT, 35 parts of PLA, and 10 parts of hydroxymethylsilane-modified starch at 175° C. to obtain a middle layer raw material;

[0045] S5, 10 parts of PBAT, 0.5 parts of p-toluonitrile, and 7 parts of hydroxymethylsilane-modified starch were mixed uniformly at 130° C. to obtain a base material;

[0046] S6. Co-extrude the surface layer raw material, the middle layer raw material and the base layer raw material at 180° C., blow mold, and cool to obtain a degradable film with a thickness ratio of surface layer: middle layer: base layer of 0.3:4:0.7.

[0047] Example 3

[0048] S1, adjusting the pH value of 100 g of cassava starch to 9 with a sodium carbonate aqueous solution, drying at 45° C. to a water content of 3 wt %, adding 5 g of (butylaminomethyl)triethoxysilane and stirring for 10 min, heating to 135° C. and reacting for 45 min, cooling, and grinding to obtain secondary aminosilane-modified starch;

[0049] S2, adjusting the pH value of 100 g of cassava starch to 9 with sodium carbonate aqueous solution, drying at 45° C. to a water content of 3 wt %, adding 5 g of 3-[bis(2-hydroxyethyl)amino]propane-triethoxysilane, stirring for 10 min, heating to 135° C., reacting for 45 min, cooling, and grinding to obtain hydroxymethylsilane-modified starch;

[0050] S3, mixing 80 parts of PLA and 8 parts of secondary aminosilane-modified starch at 175° C. to obtain a surface layer raw material;

[0051] S4, mixing 90 parts of PBAT, 15 parts of PLA, and 10 parts of hydroxymethylsilane-modified starch at 175° C. to obtain a middle layer raw material;

[0052] S5, 30 parts of PBAT, 0.5 parts of p-toluonitrile, and 12 parts of hydroxymethylsilane-modified starch were mixed uniformly at 130° C. to obtain a base material;

[0053] S6. Co-extrude the surface layer raw material, the middle layer raw material and the base layer raw material at 180° C., blow mold, and cool to obtain a degradable film with a thickness ratio of surface layer: middle layer: base layer of 0.3:4:0.7.

[0054] Example 4

[0055] S1, adjusting the pH value of 100 g of cassava starch to 9 with sodium carbonate aqueous solution, drying at 45° C. to a water content of 3 wt %, adding 3 g of (butylaminomethyl)triethoxysilane and stirring for 10 min, heating to 135° C. and reacting for 45 min, cooling, and grinding to obtain secondary aminosilane-modified starch;

[0056] S2, adjusting the pH value of 100 g of cassava starch to 9 with sodium carbonate aqueous solution, drying at 45° C. to a water content of 3 wt %, adding 3 g of N-(hydroxyethyl)-N-methylaminopropyltrimethoxysilane, stirring for 10 min, heating to 135° C., reacting for 45 min, cooling, and grinding to obtain hydroxymethylsilane-modified starch;

[0057] S3, mixing 70 parts of PLA and 5 parts of secondary aminosilane-modified starch at 175° C. to obtain a surface layer raw material;

[0058] S4, 80 parts of PBAT, 25 parts of PLA, and 10 parts of hydroxymethylsilane-modified starch were mixed uniformly at 175° C. to obtain a middle layer raw material;

[0059] S5, 20 parts of PBAT, 1.5 parts of p-toluonitrile, and 9 parts of hydroxymethylsilane-modified starch were mixed uniformly at 130° C. to obtain a base material;

[0060] S6. Co-extrude the surface layer raw material, the middle layer raw material and the base layer raw material at 180° C., blow mold, and cool to obtain a degradable film with a thickness ratio of surface layer: middle layer: base layer of 0.3:4:0.7.

[0061] Example 5

[0062] S1, adjusting the pH value of 100 g of cassava starch to 9 with sodium carbonate aqueous solution, drying at 45° C. to a water content of 3 wt %, adding 3 g of (butylaminomethyl)triethoxysilane and stirring for 10 min, heating to 135° C. and reacting for 45 min, cooling, and grinding to obtain secondary aminosilane-modified starch;

[0063] S2, adjusting the pH value of 100 g of cassava starch to 9 with sodium carbonate aqueous solution, drying at 45° C. to a water content of 3 wt %, adding 3 g of N-(hydroxyethyl)-N-methylaminopropyltrimethoxysilane, stirring for 10 min, heating to 135° C., reacting for 45 min, cooling, and grinding to obtain hydroxymethylsilane-modified starch;

[0064] S3, mixing 70 parts of PLA and 5 parts of secondary aminosilane-modified starch at 175° C. to obtain a surface layer raw material;

[0065] S4, 80 parts of PBAT, 25 parts of PLA, and 10 parts of hydroxymethylsilane-modified starch were mixed uniformly at 175° C. to obtain a middle layer raw material;

[0066] S5, 20 parts of PBAT, 2.5 parts of p-toluonitrile, and 9 parts of hydroxymethylsilane-modified starch were mixed uniformly at 130° C. to obtain a base material;

[0067] S6. Co-extrude the surface layer raw material, the middle layer raw material and the base layer raw material at 180° C., blow mold, and cool to obtain a degradable film with a thickness ratio of surface layer: middle layer: base layer of 0.3:4:0.7.

[0068] Example 6

[0069] S1, adjusting the pH value of 100 g of cassava starch to 9 with sodium carbonate aqueous solution, drying at 45° C. to a water content of 3 wt %, adding 3 g of (butylaminomethyl)triethoxysilane and stirring for 10 min, heating to 135° C. and reacting for 45 min, cooling, and grinding to obtain secondary aminosilane-modified starch;

[0070] S2, adjusting the pH value of 100 g of cassava starch to 9 with sodium carbonate aqueous solution, drying at 45° C. to a water content of 3 wt %, adding 3 g of N-(hydroxyethyl)-N-methylaminopropyltrimethoxysilane, stirring for 10 min, heating to 135° C., reacting for 45 min, cooling, and grinding to obtain hydroxymethylsilane-modified starch;

[0071] S3, mixing 70 parts of PLA and 5 parts of secondary aminosilane-modified starch at 175° C. to obtain a surface layer raw material;

[0072] S4, 80 parts of PBAT, 25 parts of PLA, and 10 parts of hydroxymethylsilane-modified starch were mixed uniformly at 175° C. to obtain a middle layer raw material;

[0073] S5, 20 parts of PBAT, 3.5 parts of p-toluonitrile, and 9 parts of hydroxymethylsilane-modified starch were mixed uniformly at 130° C. to obtain a base material;

[0074] S6. Co-extrude the surface layer raw material, the middle layer raw material and the base layer raw material at 180° C., blow mold, and cool to obtain a degradable film with a thickness ratio of surface layer: middle layer: base layer of 0.3:4:0.7.

[0075] Example 7

[0076] S1, adjusting the pH value of 100 g of cassava starch to 9 with sodium carbonate aqueous solution, drying at 45° C. to a water content of 3 wt %, adding 3 g of (butylaminomethyl)triethoxysilane and stirring for 10 min, heating to 135° C. and reacting for 45 min, cooling, and grinding to obtain secondary aminosilane-modified starch;

[0077] S2, adjusting the pH value of 100 g of cassava starch to 9 with sodium carbonate aqueous solution, drying at 45° C. to a water content of 3 wt %, adding 3 g of N-(hydroxyethyl)-N-methylaminopropyltrimethoxysilane, stirring for 10 min, heating to 135° C., reacting for 45 min, cooling, and grinding to obtain hydroxymethylsilane-modified starch;

[0078] S3, mixing 70 parts of PLA and 5 parts of secondary aminosilane-modified starch at 175° C. to obtain a surface layer raw material;

[0079] S4, 80 parts of PBAT, 25 parts of PLA, and 10 parts of hydroxymethylsilane-modified starch were mixed uniformly at 175° C. to obtain a middle layer raw material;

[0080] S5, 20 parts of PBAT, 2.5 parts of 1,4-phenylenediacetonitrile, and 9 parts of hydroxymethylsilane-modified starch were mixed uniformly at 130° C. to obtain a base material;

[0081] S6. Co-extrude the surface layer raw material, the middle layer raw material and the base layer raw material at 180° C., blow mold, and cool to obtain a degradable film with a thickness ratio of surface layer: middle layer: base layer of 0.3:4:0.7.

[0082] Example 8

[0083] S1, adjusting the pH value of 100 g of cassava starch to 9 with sodium carbonate aqueous solution, drying at 45° C. to a water content of 3 wt %, adding 3 g of (butylaminomethyl)triethoxysilane and stirring for 10 min, heating to 135° C. and reacting for 45 min, cooling, and grinding to obtain secondary aminosilane-modified starch;

[0084] S2, adjusting the pH value of 100 g of cassava starch to 9 with sodium carbonate aqueous solution, drying at 45° C. to a water content of 3 wt %, adding 3 g of N-(hydroxyethyl)-N-methylaminopropyltrimethoxysilane, stirring for 10 min, heating to 135° C., reacting for 45 min, cooling, and grinding to obtain hydroxymethylsilane-modified starch;

[0085] S3, mixing 70 parts of PLA and 5 parts of secondary aminosilane-modified starch at 175° C. to obtain a surface layer raw material;

[0086] S4, 80 parts of PBAT, 25 parts of PLA, and 10 parts of hydroxymethylsilane-modified starch were mixed uniformly at 175° C. to obtain a middle layer raw material;

[0087] S5, 20 parts of PBAT, 2.5 parts of 4-cyanoheptanedinitrile, and 9 parts of hydroxymethylsilane-modified starch were mixed uniformly at 130° C. to obtain a base material;

[0088] S6. Co-extrude the surface layer raw material, the middle layer raw material and the base layer raw material at 180° C., blow mold, and cool to obtain a degradable film with a thickness ratio of surface layer: middle layer: base layer of 0.3:4:0.7.

[0089] Example 9

[0090] S1, adjusting the pH value of 100 g of cassava starch to 9 with sodium carbonate aqueous solution, drying at 45° C. to a water content of 3 wt %, adding 3 g of (butylaminomethyl)triethoxysilane and stirring for 10 min, heating to 135° C. and reacting for 45 min, cooling, and grinding to obtain secondary aminosilane-modified starch;

[0091] S2, adjusting the pH value of 100 g of cassava starch to 9 with sodium carbonate aqueous solution, drying at 45° C. to a water content of 3 wt %, adding 3 g of N-(hydroxyethyl)-N-methylaminopropyltrimethoxysilane, stirring for 10 min, heating to 135° C., reacting for 45 min, cooling, and grinding to obtain hydroxymethylsilane-modified starch;

[0092] S3, mixing 70 parts of PLA and 5 parts of secondary aminosilane-modified starch at 175° C. to obtain a surface layer raw material;

[0093] S4, mixing 80 parts of PBAT, 25 parts of PLA, and 12 parts of hydroxymethylsilane-modified starch at 175° C. to obtain a middle layer raw material;

[0094] S5, 20 parts of PBAT, 2.5 parts of 1,4-phenylenediacetonitrile, and 9 parts of hydroxymethylsilane-modified starch were mixed uniformly at 130° C. to obtain a base material;

[0095] S6. Co-extrude the surface layer raw material, the middle layer raw material and the base layer raw material at 180° C., blow mold, and cool to obtain a degradable film with a thickness ratio of surface layer: middle layer: base layer of 0.3:4:0.7.

[0096] Example 10

[0097] S1, adjusting the pH value of 100 g of cassava starch to 9 with sodium carbonate aqueous solution, drying at 45° C. to a water content of 3 wt %, adding 3 g of (butylaminomethyl)triethoxysilane and stirring for 10 min, heating to 135° C. and reacting for 45 min, cooling, and grinding to obtain secondary aminosilane-modified starch;

[0098] S2, adjusting the pH value of 100 g of cassava starch to 9 with sodium carbonate aqueous solution, drying at 45° C. to a water content of 3 wt %, adding 3 g of N-(hydroxyethyl)-N-methylaminopropyltrimethoxysilane, stirring for 10 min, heating to 135° C., reacting for 45 min, cooling, and grinding to obtain hydroxymethylsilane-modified starch;

[0099] S3, mixing 70 parts of PLA and 5 parts of secondary aminosilane-modified starch at 175° C. to obtain a surface layer raw material;

[0100] S4, 80 parts of PBAT, 25 parts of PLA, and 15 parts of hydroxymethylsilane-modified starch were mixed uniformly at 175° C. to obtain a middle layer raw material;

[0101] S5, 20 parts of PBAT, 2.5 parts of 1,4-phenylenediacetonitrile, and 9 parts of hydroxymethylsilane-modified starch were mixed uniformly at 130° C. to obtain a base material;

[0102] S6. Co-extrude the surface layer raw material, the middle layer raw material and the base layer raw material at 180° C., blow mold, and cool to obtain a degradable film with a thickness ratio of surface layer: middle layer: base layer of 0.3:4:0.7.

[0103] Embodiment 11

[0104] S1, adjusting the pH value of 100 g of cassava starch to 9 with sodium carbonate aqueous solution, drying at 45° C. to a water content of 3 wt %, adding 3 g of (butylaminomethyl)triethoxysilane and stirring for 10 min, heating to 135° C. and reacting for 45 min, cooling, and grinding to obtain secondary aminosilane-modified starch;

[0105] S2, adjusting the pH value of 100 g of cassava starch to 9 with sodium carbonate aqueous solution, drying at 45° C. to a water content of 3 wt %, adding 3 g of N-(hydroxyethyl)-N-methylaminopropyltrimethoxysilane, stirring for 10 min, heating to 135° C., reacting for 45 min, cooling, and grinding to obtain hydroxymethylsilane-modified starch;

[0106] S3, mixing 70 parts of PLA and 5 parts of secondary aminosilane-modified starch at 175° C. to obtain a surface layer raw material;

[0107] S4, mixing 80 parts of PBAT, 25 parts of PLA, and 17 parts of hydroxymethylsilane-modified starch at 175° C. to obtain a middle layer raw material;

[0108] S5, 20 parts of PBAT, 2.5 parts of 1,4-phenylenediacetonitrile, and 9 parts of hydroxymethylsilane-modified starch were mixed uniformly at 130° C. to obtain a base material;

[0109] S6. Co-extrude the surface layer raw material, the middle layer raw material and the base layer raw material at 180° C., blow mold, and cool to obtain a degradable film with a thickness ratio of surface layer: middle layer: base layer of 0.3:4:0.7.

[0110] Example 12

[0111] S1, adjusting the pH value of 100 g of cassava starch to 9 with sodium carbonate aqueous solution, drying at 45° C. to a water content of 3 wt %, adding 3 g of (butylaminomethyl)triethoxysilane and stirring for 10 min, heating to 135° C. and reacting for 45 min, cooling, and grinding to obtain secondary aminosilane-modified starch;

[0112] S2, adjusting the pH value of 100 g of cassava starch to 9 with sodium carbonate aqueous solution, drying at 45° C. to a water content of 3 wt %, adding 3 g of N-(hydroxyethyl)-N-methylaminopropyltrimethoxysilane, stirring for 10 min, heating to 135° C., reacting for 45 min, cooling, and grinding to obtain hydroxymethylsilane-modified starch;

[0113] S3, mixing 70 parts of PLA and 5 parts of secondary aminosilane-modified starch at 175° C. to obtain a surface layer raw material;

[0114] S4, 80 parts of PBAT, 25 parts of PLA, and 20 parts of hydroxymethylsilane-modified starch were mixed uniformly at 175° C. to obtain a middle layer raw material;

[0115] S5, 20 parts of PBAT, 2.5 parts of 1,4-phenylenediacetonitrile, and 9 parts of hydroxymethylsilane-modified starch were mixed uniformly at 130° C. to obtain a base material;

[0116] S6. Co-extrude the surface layer raw material, the middle layer raw material and the base layer raw material at 180° C., blow mold, and cool to obtain a degradable film with a thickness ratio of surface layer: middle layer: base layer of 0.3:4:0.7.

[0117] Embodiment 13

[0118] S1, adjusting the pH value of 100 g of cassava starch to 9 with sodium carbonate aqueous solution, drying at 45° C. to a water content of 3 wt %, adding 3 g of (butylaminomethyl)triethoxysilane and stirring for 10 min, heating to 135° C. and reacting for 45 min, cooling, and grinding to obtain secondary aminosilane-modified starch;

[0119] S2, adjusting the pH value of 100 g of cassava starch to 9 with sodium carbonate aqueous solution, drying at 45° C. to a water content of 3 wt %, adding 3 g of N-(hydroxyethyl)-N-methylaminopropyltrimethoxysilane, stirring for 10 min, heating to 135° C., reacting for 45 min, cooling, and grinding to obtain hydroxymethylsilane-modified starch;

[0120] S3, mixing 70 parts of PLA and 5 parts of secondary aminosilane-modified starch at 175° C. to obtain a surface layer raw material;

[0121] S4, 80 parts of PBAT, 25 parts of PLA, and 15 parts of hydroxymethylsilane-modified starch were mixed uniformly at 175° C. to obtain a middle layer raw material;

[0122] S5, 20 parts of PBAT, 2.5 parts of glutaronitrile, and 9 parts of hydroxymethylsilane-modified starch were mixed uniformly at 130° C. to obtain a base material;

[0123] S6. Co-extrude the surface layer raw material, the middle layer raw material and the base layer raw material at 180° C., blow mold, and cool to obtain a degradable film with a thickness ratio of surface layer: middle layer: base layer of 0.3:4:0.7.

[0124] Embodiment 14

[0125] S1, adjusting the pH value of 100 g of cassava starch to 9 with sodium carbonate aqueous solution, drying at 45° C. to a water content of 3 wt %, adding 3 g of (butylaminomethyl)triethoxysilane and stirring for 10 min, heating to 135° C. and reacting for 45 min, cooling, and grinding to obtain secondary aminosilane-modified starch;

[0126] S2, adjusting the pH value of 100 g of cassava starch to 9 with sodium carbonate aqueous solution, drying at 45° C. to a water content of 3 wt %, adding 3 g of N-(hydroxyethyl)-N-methylaminopropyltrimethoxysilane, stirring for 10 min, heating to 135° C., reacting for 45 min, cooling, and grinding to obtain hydroxymethylsilane-modified starch;

[0127] S3, mixing 70 parts of PLA and 5 parts of secondary aminosilane-modified starch at 175° C. to obtain a surface layer raw material;

[0128] S4, 80 parts of PBAT, 25 parts of PLA, and 15 parts of hydroxymethylsilane-modified starch were mixed uniformly at 175° C. to obtain a middle layer raw material;

[0129] S5, 20 parts of PBAT, 2.2 parts of 1,4-benzenediacetonitrile, 0.3 parts of glutaronitrile, and 9 parts of hydroxymethylsilane-modified starch were mixed uniformly at 130° C. to obtain a base material;

[0130] S6. Co-extrude the surface layer raw material, the middle layer raw material and the base layer raw material at 180° C., blow mold, and cool to obtain a degradable film with a thickness ratio of surface layer: middle layer: base layer of 0.3:4:0.7.

[0131] Embodiment 15

[0132] S1, adjusting the pH value of 100 g of cassava starch to 9 with sodium carbonate aqueous solution, drying at 45° C. to a water content of 3 wt %, adding 3 g of (butylaminomethyl)triethoxysilane and stirring for 10 min, heating to 135° C. and reacting for 45 min, cooling, and grinding to obtain secondary aminosilane-modified starch;

[0133] S2, adjusting the pH value of 100 g of cassava starch to 9 with sodium carbonate aqueous solution, drying at 45° C. to a water content of 3 wt %, adding 3 g of N-(hydroxyethyl)-N-methylaminopropyltrimethoxysilane, stirring for 10 min, heating to 135° C., reacting for 45 min, cooling, and grinding to obtain hydroxymethylsilane-modified starch;

[0134] S3, mixing 70 parts of PLA and 5 parts of secondary aminosilane-modified starch at 175° C. to obtain a surface layer raw material;

[0135] S4, 80 parts of PBAT, 25 parts of PLA, and 15 parts of hydroxymethylsilane-modified starch were mixed uniformly at 175° C. to obtain a middle layer raw material;

[0136] S5, 20 parts of PBAT, 2 parts of 1,4-benzenediacetonitrile, 0.5 parts of glutaronitrile, and 9 parts of hydroxymethylsilane-modified starch were mixed uniformly at 130° C. to obtain a base material;

[0137] S6. Co-extrude the surface layer raw material, the middle layer raw material and the base layer raw material at 180° C., blow mold, and cool to obtain a degradable film with a thickness ratio of surface layer: middle layer: base layer of 0.3:4:0.7.

[0138] Example 16

[0139] S1, adjusting the pH value of 100 g of cassava starch to 9 with sodium carbonate aqueous solution, drying at 45° C. to a water content of 3 wt %, adding 3 g of (butylaminomethyl)triethoxysilane and stirring for 10 min, heating to 135° C. and reacting for 45 min, cooling, and grinding to obtain secondary aminosilane-modified starch;

[0140] S2, adjusting the pH value of 100 g of cassava starch to 9 with sodium carbonate aqueous solution, drying at 45° C. to a water content of 3 wt %, adding 3 g of N-(hydroxyethyl)-N-methylaminopropyltrimethoxysilane, stirring for 10 min, heating to 135° C., reacting for 45 min, cooling, and grinding to obtain hydroxymethylsilane-modified starch;

[0141] S3, mixing 70 parts of PLA and 5 parts of secondary aminosilane-modified starch at 175° C. to obtain a surface layer raw material;

[0142] S4, 80 parts of PBAT, 25 parts of PLA, and 15 parts of hydroxymethylsilane-modified starch were mixed uniformly at 175° C. to obtain a middle layer raw material;

[0143] S5, 20 parts of PBAT, 1.5 parts of 1,4-phenyldiacetonitrile, 1 part of glutaronitrile, and 9 parts of hydroxymethylsilane-modified starch were mixed uniformly at 130° C. to obtain a base material;

[0144] S6. Co-extrude the surface layer raw material, the middle layer raw material and the base layer raw material at 180° C., blow mold, and cool to obtain a degradable film with a thickness ratio of surface layer: middle layer: base layer of 0.3:4:0.7.

[0145] Comparative Example 1

[0146] The only difference from Example 1 is:

[0147] S3, mixing 70 parts of PLA and 5 parts of secondary aminosilane-modified starch at 175° C. to obtain a surface layer raw material;

[0148] S4, 80 parts of PBAT, 25 parts of PLA, 0.5 parts of p-toluonitrile, and 10 parts of hydroxymethylsilane-modified starch were mixed uniformly at 175° C. to obtain a middle layer raw material;

[0149] S5, 20 parts of PBAT, 0.5 parts of p-toluonitrile, and 9 parts of hydroxymethylsilane-modified starch were mixed uniformly at 130° C. to obtain a base material;

[0150] S6. Co-extrude the surface layer raw material, the middle layer raw material and the base layer raw material at 180° C., blow mold, and cool to obtain a degradable film with a thickness ratio of surface layer: middle layer: base layer of 0.3:4:0.7.

[0151] Comparative Example 2

[0152] The only difference from Example 1 is:

[0153] S3, mixing 70 parts of PLA and 5 parts of secondary aminosilane-modified starch at 175° C. to obtain a surface layer raw material;

[0154] S4, 80 parts of PBAT, 25 parts of PLA, 0.5 parts of p-toluonitrile, and 10 parts of hydroxymethylsilane-modified starch were mixed uniformly at 175° C. to obtain a middle layer raw material;

[0155] S5, mixing 20 parts of PBAT and 9 parts of hydroxymethylsilane-modified starch at 130° C. to obtain a base material;

[0156] S6. Co-extrude the surface layer raw material, the middle layer raw material and the base layer raw material at 180° C., blow mold, and cool to obtain a degradable film with a thickness ratio of surface layer: middle layer: base layer of 0.3:4:0.7.

[0157] The degradable films with a thickness of 0.01 mm obtained in Examples 1 to 16 and Comparative Examples 1 to 2 were tested for tensile load and right-angle tear load according to the method in GB / T 35795-2017; the test results are recorded in Table 1.

[0158] Table 1 Tensile load and right-angle tear load of degradable films

[0159]

[0160] It can be seen from Table 1 that the degradable films provided by Examples 1 to 16 of the present invention have high tensile load and right-angle tear load, which meet the requirements of various indicators in GB / T 35795-2017.

[0161] The tensile load and right-angle tear load of the degradable films obtained in Examples 1 to 16 are higher than those in Comparative Examples 1 to 2, indicating that the strength of the degradable film can be improved by using PLA and secondary aminosilane-modified starch in the surface layer, PBAT, PLA and hydroxymethylsilane-modified starch in the middle layer, and PBAT, nitrile-containing compounds and hydroxymethylsilane-modified starch in the base layer.

[0162] The tensile load and right-angle tear load of the degradable film obtained in Examples 4 to 5 are higher than those in Example 1 and Example 6, indicating that the mass ratio of hydroxymethylsilane-modified starch to the nitrile-containing compound in the base layer is 9:1.5 to 2.5, which can further improve the strength of the degradable film.

[0163] The tensile load and right-angle tear load of the degradable film obtained in Example 7 are higher than those in Example 5 and Example 8, indicating that the compound containing a nitrile group is a compound containing two nitrile groups, which can further improve the strength of the degradable film.

[0164] The tensile load and right-angle tear load of the degradable film obtained in Examples 9 to 11 are higher than those in Example 7 and Example 12, indicating that the mass ratio of secondary aminosilane-modified starch to hydroxymethylsilane-modified starch in the middle layer is 5:12 to 17, which can further improve the strength of the degradable film.

[0165] The tensile load and right-angle tear load of the degradable film obtained in Example 15 are higher than those in the other examples, indicating that the compound containing a nitrile group is a compound containing a nitrile group containing a benzene ring and a compound containing a nitrile group without a benzene ring in a mass ratio of 2:0.5, which can further improve the strength of the degradable film.

[0166] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A degradable film, comprising a surface layer, an intermediate layer and a base layer from top to bottom, characterized in that: The raw materials of the surface layer include the following components in parts by weight: 60-80 parts of PLA and 3-8 parts of secondary aminosilane-modified starch; The raw materials of the intermediate layer include the following components in parts by mass: 70-90 parts of PBAT, 15-35 parts of PLA, and 10-20 parts of silane-modified starch. The silane-modified starch in the intermediate layer is N-(hydroxyethyl)-N-methylaminopropyltrimethoxysilane-modified starch or 3-[bis(2-hydroxyethyl)amino]propane-triethoxysilane-modified starch; The raw materials of the base layer include the following components in parts by mass: 10 to 30 parts of PBAT, 0.5 to 3.5 parts of a compound containing a nitrile group, and 7 to 12 parts of silane-modified starch. The silane-modified starch in the base layer is N-(hydroxyethyl)-N-methylaminopropyltrimethoxysilane-modified starch or 3-[bis(2-hydroxyethyl)amino]propane-triethoxysilane-modified starch.

2. A degradable film according to claim 1, characterized in that: The mass ratio of the silane-modified starch to the compound containing a nitrile group in the base layer is 9:1.5-2.

5.

3. A degradable film according to claim 2, characterized in that: The compound containing a nitrile group is a compound containing two nitrile groups.

4. A degradable film according to claim 1, characterized in that: The mass ratio of the secondary aminosilane modified starch to the silane modified starch in the middle layer is 5:12-17.

5. A degradable film according to claim 3, characterized in that: The compound containing a nitrile group comprises a compound containing a benzene ring and a nitrile group and a compound containing no benzene ring and a nitrile group in a mass ratio of 2:0.

5.

6. A degradable film according to claim 1, characterized in that: The raw materials of the silane-modified starch in the base layer include silane and starch in a mass ratio of 1 to 5:

100.

7. The degradable film according to claim 1, characterized in that: The raw materials of the secondary aminosilane-modified starch in the surface layer include secondary aminosilane and starch in a mass ratio of 1 to 5:

100.

8. The degradable film according to claim 1, characterized in that: The raw materials of the silane-modified starch in the intermediate layer include silane and starch in a mass ratio of 1 to 5:

100.

9. The method for preparing a degradable film according to any one of claims 1 to 8, characterized in that: The following steps are involved: The raw materials of the surface layer, the raw materials of the middle layer and the raw materials of the base layer are melted and mixed uniformly, and then co-extruded, blow-molded and cooled to obtain a degradable film.

10. Use of the degradable film according to any one of claims 1 to 8 or the degradable film prepared by the preparation method according to claim 9 in ground film.

Citation Information

Patent Citations

  • Preparation method of degradable composite doped with fluffy bamboo fiber

    CN105802169A

  • Degradable agricultural insect-repelling and grass-inhibiting film and preparation method thereof

    CN115521594A